Microbial radiosensitization using combined treatments of essential oils and irradiation- part B: Comparison between gamma-ray and X-ray at different dose rates - Shankar, Shiv; Follett, Peter; Ayari, Samia; Hossain, Farah; Salmieri, Stephane; Lacroix, Monique
Stored rice and rice products are prone to contamination by pathogenic fungi and bacteria such asAspergillus niger, Bacillus cereus, and Paenibacillus amylolyticus. Treatment with antimicrobial essential oils (EOs)and irradiation are options to control spoilage organisms. Microbial samples with or without fumigation with an oregano/thyme EO mixture were irradiated at 0.5, 0.75, 1.0, 1.5, 2.0, 2.5, 3.0 and 3.5 kGy for calculation of a D10 value. The relative sensitivity was calculated as the ratio of D10 values for the irradiation plus oregano and thyme EO combination and irradiation alone treatments. In all cases, irradiation plus fumigation with the oregano and thyme EO mixture showed increased efficacy compared with irradiation alone. The relative sensitivity of?-ray irradiation against A. nigerwas 1.22, 1.33, and 1.24 for radiation dose rates of 10.445, 4.558, and 0.085 kGy/h, respectively, however againstB. cereusit was 1.28, 1.45, and 1.49, and against P. amylolyticusit was 1.35, 1.33, and 1.38, for respective?-ray irradiation dose rates. The relative sensitivity of X-ray irradiation againstA. niger, B. cereus,andP. amylolyticuswas 1.63, 1.21, and 1.31, respectively, at the X-ray dose rate of 0.76 kGy/h. The results showed that the relative sensitivity of?-ray irradiation was higher against the two bacteria than the fungus, whereas X-ray showed higher sensitivity against the fungus than the two bacteria. There was no consistent positive or negative relationship between dose rate and relative sensitivity. The results demonstrated the potential of an oregano and thyme EOs mixture as an antimicrobial agent and its efficacy to increase the radiosensitization of A. niger, B. cereus,andP. amylolyticusduring?-ray or X-ray irradiation treatments.
Keywords: RADIOSENSITIZATION; ASPERGILLUS NIGER; BACILLUS CEREUS; PAENIBACILLUS AMYLOLYTICUS; GAMMA-RAY; X-RA